Efektivitas Pembelajaran Kooperatif Model Take and Give dalam Meningkatkan Keterampilan Menyimak Peserta didik MTs Nurul Hidayah Al-Falah / The Effectiveness of the Take and Give Cooperative Learning Model in Improving the Listening Skills of Students at MTs Nurul Hidayah Al-Falah - Hasyim Asyari; Hamzah Hamzah; Muftihatur Rahmah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
The purpose of this study was to determine the listening ability of seventh-grade students at MTs Nurul Hidayah Al-Falah before using the Take and Give cooperative learning model. This study also aims to determine students' listening skills during the implementation of the Take and Give model, as well as to determine the effectiveness of this model in improving students' listening skills. This study used a quantitative research method with a pre-experimental one-group pretest-posttest design. The study population included all students of MTs Nurul Hidayah Al-Falah, with a research sample of 29 seventh-grade students selected using a saturated sampling technique. Data collection methods included pretest, posttest, and observation. Data analysis techniques included validity and reliability tests, T-tests, and N-gain analysis. The results showed that the average pretest score of students' listening ability was 61.4, which increased to 83.5 in the posttest, indicating a significant increase. The implementation of the Take and Give model effectively improved students' listening ability, evidenced by the N-gain score of 0.5915 which was categorized as quite effective. Statistical analysis shows tcount = 2.193 > ttable = 2.05183, which confirms significant effectiveness. Therefore, the Take and Give model has a positive impact on Arabic language learning in the context of listening skills.Tujuan penelitian ini adalah untuk mengetahui keterampilan menyimak peserta didik kelas VII di MTs Nurul Hidayah Al-Falah sebelum menggunakan model pembelajaran kooperatif Take and Give. Penelitian ini juga bertujuan untuk mengetahui keterampilan menyimak peserta didik selama implementasi model Take and Give, serta untuk mengetahui efektivitas model ini dalam meningkatkan kemampuan mendengarkan peserta didik. Penelitian ini menggunakan metode penelitian kuantitatif dengan desain pra-eksperimental satu kelompok pretest-posttest. Populasi penelitian meliputi seluruh peserta didik MTs Nurul Hidayah Al-Falah, dengan sampel penelitian sebanyak 29 peserta didik kelas VII yang dipilih menggunakan teknik sampling jenuh. Metode pengumpulan data meliputi pretest, posttest, dan observasi. Teknik analisis data meliputi uji validitas dan reliabilitas, uji T, dan analisis N-gain. Hasil penelitian menunjukkan bahwa rata-rata skor pretest kemampuan mendengarkan peserta didik adalah 61,4, yang meningkat menjadi 83,5 pada posttest, menunjukkan peningkatan yang signifikan. Penerapan model Take and Give secara efektif meningkatkan kemampuan mendengarkan peserta didik, dibuktikan dengan skor N-gain sebesar 0,5915 yang dikategorikan cukup efektif. Analisis statistik menunjukkan t count = 2,193 > t table = 2,05183, yang menegaskan efektivitas yang signifikan. Oleh karena itu, model Take and Give memiliki dampak positif pada pembelajaran bahasa Arab dalam konteks keterampilan menyimak.